Mona Passage : a novel - Bardenwerper, Thomas "Buddy" (Syracuse University Press, 2021)
"Selected as the runner-up for the inaugural Veterans Writing Award, Bardenwerper's novel explores the friendship between Pat, an officer in the Coast Guard, and Galán, a Cuban emigrant"--